The YOPP Final Summit: Assessing Past and Forecasting Future Polar Prediction Research - Wilson, Jeff; Jung, Thomas; Bazile, Eric; Bromwich, David; Casati, Barbara; Day, Jonathan; de Coning, Estelle; Eayrs, Clare; Grumbine, Robert; Ioue, Jun; Khalsa, Siri Jodha S.; Kristiansen, Jorn; et al. (Bulletin of the American Meteorological Society, 2023)
International audience